2017
DOI: 10.1111/1751-7915.12731
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of complete genome sequence and major surface antigens of Neorickettsia helminthoeca, causative agent of salmon poisoning disease

Abstract: Summary Neorickettsia helminthoeca, a type species of the genus Neorickettsia, is an endosymbiont of digenetic trematodes of veterinary importance. Upon ingestion of salmonid fish parasitized with infected trematodes, canids develop salmon poisoning disease (SPD), an acute febrile illness that is particularly severe and often fatal in dogs without adequate treatment. We determined and analysed the complete genome sequence of N. helminthoeca: a single small circular chromosome of 884 232 bp encoding 774 potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 147 publications
1
16
0
Order By: Relevance
“…Phylogenetic analysis revealed that only 10 of the isolates were N. risticii strains, whereas the remaining two isolates (Fin17 and Tom16) were a previously uncharacterized Neorickettsia sp. The results were corroborated by whole-genome sequencing of Fin17 and genomic comparison with N. risticii, N. sennetsu, and N. helminthoeca (21,45,46,48). Experimental inoculation of Fin17 clearly showed that it can infect horses and cause PHF or subclinical infection.…”
Section: Discussionmentioning
confidence: 67%
See 4 more Smart Citations
“…Phylogenetic analysis revealed that only 10 of the isolates were N. risticii strains, whereas the remaining two isolates (Fin17 and Tom16) were a previously uncharacterized Neorickettsia sp. The results were corroborated by whole-genome sequencing of Fin17 and genomic comparison with N. risticii, N. sennetsu, and N. helminthoeca (21,45,46,48). Experimental inoculation of Fin17 clearly showed that it can infect horses and cause PHF or subclinical infection.…”
Section: Discussionmentioning
confidence: 67%
“…These findings suggest that the multiple ssa genes in Fin17, N. risticii, and N. sennetsu arose as gene duplication events after the two species diverged from N. helminthoeca. Ssas have extensive intramolecular sequence repeats (34,45,46,48). Notably, the Fin17/Tom16 16S rRNA and P51 gene sequences were phylogenetically separated from those of other PHF-related strains, whereas the presence of Ssa3 repeat structures was similar to those of the N. risticii strains and distinct from those of N. sennetsu and the SF agents, suggesting that Ssa3 may be involved in PHF infection and pathogenesis.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations